Desemulsificação de petróleos assistida por ultrassom e posterior caracterização das fases água e óleo - Antes, Fabiane Goldschmidt (2011)
The effect of ultrasound (US) for demulsification of crude oils with different characteristics (viscosity, density e water content) was investigated, without using chemical demulsifier. Initially, the treatment using US was evaluated, using direct or indirect (using water as US propagation medium) application with probes. Water separation from emulsions was only verified when US was indirectly applied. Therefore, indirect US treatment was studied, using different systems. Experiments were carried out using ultrasonic baths with power of 100 or 200 W (frequency of 25 and 45 or 35 and 130 kHz) and cup horn systems with power of 130 and 750 W (frequency of 20 kHz). The best conditions of amplitude, time and temperature of US treatment were optimized. Synthetic crude oil emulsions of two crude oils were prepared with water content of 12, 35 and 50% and median drop size distribution of 5, 25 and 50 μm. Moreover, natural crude oil emulsions with water content of 12.1 ± 0.1 and 33.5 ± 0.5% (API gravity of 11.1 and 10.8, respectively) were evaluated. For synthetic crude oil emulsions, using cup horn systems, demulsification efficiencies between 40 and 50% were obtained, using 60 and 20% of amplitude for the 130 and 750 W systems, respectively. Using ultrasonic baths (frequencies of 25, 35 and 45 kHz), efficiencies between 50 and 60% were obtained, with 100% amplitude. At 130 kHz, no water separation from crude oil emulsions was observed. For natural crude oil emulsions, efficiencies better than 70% were obtained using cup horn systems or ultrasonic baths (for crude oil with initial water content of 12.1 ± 0.1%). Water and oil phases separated from crude oil emulsions using US were also characterized. It was observed that acidity, metals and sulfur content did no change after treatment with US. Additionally, the separated water was analysed using ion chromatography and gas chromatography coupled to mass spectrometry (after derivatization) to evaluate a possible migration of acid species to the water phase during US treatment.